Social Inequality and the Pandemic: An Analysis of the Photographs Shared by @covidphotobrazil and @everydaybrasil Profiles - Araujo, Camila Leite de; Oliveira, Juliana Lira de (Seven Editora, 2023)
The objective of this research is to discuss the central role of digital photography as a media that provokes reflections, discussions, debates, and possibly empathy. It is intended to analyze the social function of photographic research during the Covid-19 pandemic in Brazil through the Instagram platform and discuss the relationship between social inequality and pandemic. For the selection of the images, we chose the profiles @covidphotobrazil and @everydaybrasil, which catalog and share images about the pandemic, made by different authors and in different regions. The analysis was made in the light of discussions on the dimensions of iconology and iconography by Panofsky (2012) and adapted to photography by Kossoy (1999). We analyzed12 photographs, and from them we discussed political and social contexts of social inequality in Brazil, about the worsening of unemployment, hunger, inflation, and the political crisis in the context. We also discussed hunger, education, public transport, housing, employment and basic sanitation. As a result, we consider that the photographs are invitations to reflect on the reality of the north of the country in coping with the pandemic. The role of social science that investigates the data and information that contextualize images in contemporary history is considered extremely important. The analyses made are subjective and different looks on these same can perceive things that have gone unnoticed. The collective debate of the images that mark the Covid-19 pandemic is necessary precisely for this reason. We regret that the uses of the platform do not make explicit or bring the debate in the comments linked to the images we analyzed. This is partly due to the proposal of the platform and its audience, and partly due to the visual illiteracy of our society. Still, the comments on the images register a collective cry for social justice and express the Brazilian’s faith in the divine force to solve the public health crisis aggravated by the political and economic crises. DOI:https://doi.org/10.56238/emerrelcovid19-062